Fast Transmission Matrix Measurement of a Multimode Optical Fiber With Common Path Reference - Raphael Florentin; Vincent Kermene; Agnes Desfarges-Berthelemot; Alain Barthelemy (IEEE Photonics Journal, 2018)
We report an improved scheme for the measurement of the transmission matrix of multimode waveguides in which the reference field copropagates with the signal wave. The performance of the technique is demonstrated with the measurement of a 1.6-m long multimode optical fiber guiding 104 LP modes at 1064 nm. The transmission matrix permitted efficient focusing of the light delivered at the fiber output as well as shaping in the fiber's transmission channels.